Climate, environment and human behaviour in the Middle Palaeolithic of Abrigo de la Quebrada (Valencia, Spain): The evidence from charred plant and micromammal remains. (1st August 2019) - Carrión Marco, Yolanda; Guillem Calatayud, Pere; Eixea, Aleix; Martínez-Varea, Carmen M.; Tormo, Carmen; Badal, Ernestina; Zilhão, João; Villaverde, Valentín
Abstract: The Abrigo de la Quebrada rock shelter was occupied by Neanderthal groups during the early Upper Pleistocene, yielding evidence for their subsistence practices and local resource exploitation. This paper focuses on the plant macroremains and the micromammals, which provide information about occupation patterns, the surrounding landscape, the use of resources, and the environment. Mountain pine forests and permanent grass formations containing humid zones and open spaces that would have harboured an eurythermal microfauna were the dominant landscape type. Cold-climate pines provided most of the firewood. The data are consistent with a recurrent, seasonal occupation pattern, in which the rock shelter was used for short periods in the context of an annual round characterized by a high degree of mobility. Highlights: Abrigo de la Quebrada was occupied by Neanderthals during the early Upper Pleistocene. Plant macroremains and micromammals analyses combined are presented. Cryophilous pines provided most of the firewood, revealing cold environmental conditions. Micromammals support the existence of open forests and suggest a sporadic human occupation. The shelter was used recurrently and for short periods, supporting a high degree of mobility.